Unsteady hydrodynamic characteristics control of turbine blades by the vortex generators - Jia, Guotao; Chen, Cong; Wang, Lu; Wang, Pengzhong; Huang, Bin; Wu, Rui (Ocean engineering, 2025)
The horizontal axis tidal turbines (HATT) are subject to the intricacies of the marine environment, which includes the impact of large waves, high-intensity turbulence, and shear flow. These elements contribute to the unsteady hydrodynamic characteristics of the turbine blades, manifesting as load fluctuations, stall delays, and dynamic stalls. As a result, the HATT experiences severe power fluctuations, which diminish the quality of power generation and directly affect the reliability of the power grid and transmission system. Moreover, these fluctuations induce significant fatigue loads that impact various structures and components of the HATT, thereby reducing its service life and reliability. Controlling the unsteady hydrodynamic characteristics of the blades is crucial for enhancing the lifespan and operational stability of the turbine. In light of these challenges, the present study employs large eddy simulation (LES) numerical simulation techniques to delve into the unsteady hydrodynamic characteristics of HATT blades affected by turbulent flow, with a focus on the control exerted by vortex generators (VGs). The study scrutinizes how VGs manage flow separation on the blade surface under unstable inflow conditions and compares this to the hydrodynamic performance fluctuations observed with smooth blades. The findings reveal that VGs are capable of significantly reducing the unsteady hydrodynamic fluctuations on HATT blades and the associated flow separation on blade surfaces. When compared to smooth blades, the average fluctuation of the power coefficient for blades equipped with VGs has been diminished by 26.7%, the average fluctuation of the thrust coefficient has been reduced by 43.95%, and the average fluctuation of the blade root bending moment coefficient has been decreased by 26.6%. Additionally, the implementation of VGs has led to an average increase in the power coefficient of the blades by 5.8% at a tip-speed ratio of 2 and by 9.8% at a tip-speed ratio of 7. These results underscore the potential of VGs in enhancing the performance and reliability of HATTs in the face of challenging marine conditions. •The unsteady hydrodynamic characteristics of the blades on the first megawatt-scale unit in China were study.•The study analyzed the influence of vortex generators on the unsteady hydrodynamic characteristics of the HATT blades.•The vortex generators significantly reduces the unsteady load fluctuation of the blade.